Surgical and orthodontic rapid palatal expansion in adults using Glassman’s technique: retrospective study - R. Schimming,* K.-U. Feller,* K. Herzmann,* U. Eckelt (Blackwell Synergy, 2000)
A permanent increase in maxillary transverse width is attained routinely in children and adolescents using orthodontic expansion appliances and retention,1,2 and this treatment does not normally cause any problem. However, in skeletally mature adults, attempts at orthopaedic rapid maxillary expansion often cause appreciable problems.